METHODS AND RISK FACTORS FOR EXAMINING PATIENTS WITH GOUT (Modern education and development, 2025)
Gout is a crystal-deposition disease that results from chronic elevation of uric acid levels above the saturation point for monosodium urate (MSU) crystal formation. Initial presentation is mainly severely painful episodes of peripheral joint synovitis (acute self-limiting 'attacks') but joint damage and deformity, chronic usage-related pain and subcutaneous tophus deposition can eventually develop. The global burden of gout is substantial and seems to be increasing in many parts of the world over the past 50 years. However, methodological differences impair the comparison of gout epidemiology between countries. In this comprehensive Review, data from epidemiological studies from diverse regions of the world are synthesized to depict the geographic variation in gout prevalence and incidence. Key advances in the understanding of factors associated with increased risk of gout are also summarized. The collected data indicate that the distribution of gout is uneven across the globe, with prevalence being highest in Pacific countries. Developed countries tend to have a higher burden of gout than developing countries, and seem to have increasing prevalence and incidence of the disease. Some ethnic groups are particularly susceptible to gout, supporting the importance of genetic predisposition. Socioeconomic and dietary factors, as well as comorbidities and medications that can influence uric acid levels and/or facilitate MSU crystal formation, are also important in determining the risk of developing clinically evident gout.